Storytelling as a Didactic Proposal to Approach Culture Topics in a Fifth Graders' Classroom - Esteban Nuñez, María Teresa; Gómez Ríos, Ana Victoria (Universidad Pedagógica y Tecnológica de Colombia, 2019)
This research study was developed with ten fifth graders in the primary School Inem Carlos Arturo Torres, headquarters Las Américas, in Tunja, Colombia. The objectives of this study were to guide students to gain more knowledge about other cultures as well as their own one, to become aware of cultural differences and to develop more positive and accepting perceptions of different cultures. In this regard, some stories were narrated using big-books which were designed into the English language classroom. The instruments used in this action research to collect data were student’s artifacts, group discussions, and two surveys. Findings revealed that the stories impacted directly on students’ knowledge and understanding of other cultures as well as of the Colombian one. This strategy also helped them to build their vocabulary and to transform the way these kids were used to develop the English classes. With this activity they found their classes more interesting and dynamic.